PENGARUH SENAM PROLANIS TERHADAP KADAR GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE 2 - Dwiharini Puspitaningsih; Ika Suhartanti; Lili Wahyuni (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2025)
Type 2 diabetes mellitus is a chronic disease characterized by elevated blood sugar levels due to insulin resistance or inadequate insulin production. This condition affects the body's ability to use sugar (glucose) as an energy source. Prolanis exercises are one way to lower blood sugar levels. This study aimed to determine the effect of Prolanis exercises on blood sugar levels in patients with Type 2 Diabetes Mellitus at the Cita Mulia Mojokerto outpatient clinic. This study used a pre-experimental design with a one-group pretest-posttest design. A sample of 30 people was selected using accidental sampling. Data were analyzed using univariate analysis and bivariate analysis using the Wilcoxon signed-rank test. The results showed that almost half of the respondents adhered to Prolanis exercise with random blood sugar levels in the good category (43.3%). In addition, almost half of the respondents had random blood sugar levels in the range of 110–159 mg/dL (46.7%). The results of statistical tests showed an effect of Prolanis exercise on random blood sugar levels in patients with Type 2 Diabetes Mellitus (p=0.000). Physical activity through exercise has been shown to increase insulin sensitivity, thereby reducing blood glucose levels. Physical activity increases insulin levels, thereby reducing blood sugar levels. Health services need to provide motivational support to the community to participate in preventive activities such as exercise to further raise public awareness of the importance of consistently participating in Diabetes Mellitus control activities.